Techno-Da'i and The Qur’anic Based Social Integration Building - Nur Arfiyah Febriani; Zaenuddin Hudi Prasojo; Badru Tamam (UIN Sunan Kalijaga Yogyakarta, 2020)
Modern society tends to be techno-centric. Technology removes geographical distance and other physical restrictions in communication. Therefore, this matter must be responded by the preachers to reach the